2019
DOI: 10.4187/respcare.06352
|View full text |Cite
|
Sign up to set email alerts
|

Safety of High-Flow Nasal Cannula Outside the ICU for Previously Healthy Children With Bronchiolitis

Abstract: BACKGROUND: High-flow nasal cannula (HFNC), a form of noninvasive respiratory support, is effective for the treatment of respiratory distress in ICUs. Although HFNC has been used outside of the ICU, there is little research that examines its safety in this less-monitored setting. METHODS: Children < 24 months old admitted with bronchiolitis to a pediatric floor at a tertiary care center from April 1 2013, to March 31 2015, were identified by using standard diagnostic codes. Exclusion criteria were concomitant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…from the PICU where it was introduced, to the paediatric wards and emergency departments (EDs), 4 7 where it is being used as first-line treatment. 8 Emerging evidence from small observational studies has pointed to the safety of HFNC in the less closely monitored ward setting as opposed to PICU, [8][9][10][11] and others have retrospectively identified potential reasons for failure of ward-based HFNC therapy. 12 However, this trend towards increasing use of HFNC outside of PICU is despite a lack of clear evidence demonstrating its superiority over conventional treatments, specifically standard oxygen therapy (SOT) and continuous positive airways pressure (CPAP).…”
Section: Open Accessmentioning
confidence: 99%
“…from the PICU where it was introduced, to the paediatric wards and emergency departments (EDs), 4 7 where it is being used as first-line treatment. 8 Emerging evidence from small observational studies has pointed to the safety of HFNC in the less closely monitored ward setting as opposed to PICU, [8][9][10][11] and others have retrospectively identified potential reasons for failure of ward-based HFNC therapy. 12 However, this trend towards increasing use of HFNC outside of PICU is despite a lack of clear evidence demonstrating its superiority over conventional treatments, specifically standard oxygen therapy (SOT) and continuous positive airways pressure (CPAP).…”
Section: Open Accessmentioning
confidence: 99%
“…Initially developed for preterm infants, the application of this technology is rapidly spreading to include pediatric patients with various indications, including hospitalized bronchiolitis, 5 asthma, postextubation support, 6 and even adult hypoxemic respiratory failure 4 . In small children particularly, HFNC therapy may be better tolerated than traditional modes of noninvasive support, such as continuous positive airway pressure (CPAP) and bilevel positive airway pressure (BiPAP) in part owing to its smaller nasal prong interface allowing activities like breastfeeding with greater ease 7,8 . In a recent multicenter, randomized clinical trial addressing acutely ill children aged 0–15 years assessed to require noninvasive respiratory support, HFNC compared with CPAP met the criterion for noninferiority for time to liberation from respiratory support 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…4 In small children particularly, HFNC therapy may be better tolerated than traditional modes of noninvasive support, such as continuous positive airway pressure (CPAP) and bilevel positive airway pressure (BiPAP) in part owing to its smaller nasal prong interface allowing activities like breastfeeding with greater ease. 7,8 In a recent multicenter, randomized clinical trial addressing acutely ill children aged 0-15 years assessed to require noninvasive respiratory support, HFNC compared with CPAP met the criterion for noninferiority for time to liberation from respiratory support. 9,10 The rising acceptance of HFNC has led to its increasing use outside the intensive care setting.…”
Section: Introductionmentioning
confidence: 99%
“…The shortened duration of invasive ventilation was demonstrated in a study regarding the implementation of HHFNC on a PICU [ 9 ]. Recently HHFNC has been used in more various settings such as ward and transport [ 10 13 ]. Previous studies have reported the safety of HHFNC use during interhospital transport [ 14 ], and a reduced requirement of invasive ventilation during transport [ 7 ].…”
Section: Introductionmentioning
confidence: 99%